Pneumatology in the Lukan corpus: mapping the pneumatological diversity in the Old Testament and in the Middle Judaism - Yan, Anderson (Vox Scripturae - Revista Teológica Internacional, 2016)
This article will be divided in three parts. The first part attempts to map the bases of the pneumatology presented at the Lukan corpus, which will be examined in parts two and three. This essay focuses on the biblical-theological issue, analysing how the Old Testament borrowed pneumatological concepts available in the Ancient Near East and adapted the term חור within the development of its own pneumatology. This study continues by examining the reception of the term חור, mostly translated as πνευμα, in the Middle Judaism as it was essential part of hermeneutical horizon of the New Testament. The conclusions of this essay point to a pneumatological diversity which started in the Old Testament and evolves in the Middle Judaism. This pneumatological diversity is also shared in the New Testament.